Selective and nonselective neuronal NOS inhibitors impair cognitive function in the three panel runway and passive avoidance tasks in rats - ARICIOĞLU, FEYZA (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The aim of this study was to compare the effects of both neuronal NOS (nNOS) and inducible NOS (iNOS) inhibitor 2-iminobiotin, with the more selective nNOS inhibitor N-omega-propyl-L-arginine (NPLA) and selective inducible NOS (iNOS) inhibitor aminoguanidine, on emotional learning, working memory and reference memory, by using three panel runway and passive avoidance paradigm in order to clarify the role of distinct isoforms of NOS in the regulation of learning and memory functions. NPLA and 2-iminobiotin significantly increased the number of errors and latency of working and reference memory performances of rats in three panel runway paradigm and impairs retention for the passive avoidance task. However, aminoguanidine did not affect cognitive functions in three panel runway and passive avoidance test. The effect of NPLA and 2-iminobiotin was reversed by pretreatment with a NOS substrate L-arginine. In conclusion, NPLA and 2-iminobiotin impaired cognitive functions in different kind of tasks used in this study and the effect of NPLA and 2-iminobiotin was found to be NO-dependent. Our results may confirm that nNOS plays the key role on emotional learning, working memory and reference memory in rats. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: N-omega-propyl L-Arginine; 2-iminobiotin; Aminoguanidine; Learning; Memory; Three panel runway; Passive avoidance; NITRIC-OXIDE SYNTHASE; LONG-TERM POTENTIATION; PROPYL-L-ARGININE; MEMORY FORMATION; WORKING-MEMORY; HYPOXIA; 7-NITROINDAZOLE; HIPPOCAMPUS; ISCHEMIA; MAZE